Rehabilitative treatment of cleft lip and palate: experience of the Hospital for Rehabilitation of Craniofacial Anomalies/USP (HRAC/USP) - Part 5: Institutional outcomes assessment and the role of the Laboratory of Physiology (Journal of Applied Oral Science, 2013)
The Laboratory of Physiology provides support for the diagnosis of functional disorders associated with cleft lip and palate and also conducts studies to assess, objectively, the institutional outcomes, as recommended by the World Health Organization. The Laboratory is conceptually divided into three units, namely the Unit for Upper Airway Studies, Unit for Stomatognathic System Studies and the Unit for Sleep Studies, which aims at analyzing the impact of different surgical and dental procedures on the upper airways, stomatognathic system and the quality of sleep of individuals with cleft lip and palate. This paper describes the main goals of the Laboratory in the assessment of procedures which constitute the basis of the rehabilitation of cleft lip and palate, i.e., Plastic Surgery, Orthodontics and Maxillofacial Surgery and Speech Pathology.